2022
DOI: 10.3389/fpsyg.2022.855704
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Dignity of Advanced Cancer Patients and Its Relationship to Sociodemographic, Clinical, and Psychological Factors

Abstract: ObjectiveLoss of dignity is one of the main reasons for wishing for an early death in patients with incurable diseases such as cancer and is strongly associated with psychological distress and loss of quality of life. The present study aims to analyze the perceived dignity of patients with advanced cancer undergoing systemic treatment and their relationship with sociodemographic, clinical, and psychological factors.MethodsA prospective, cross-sectional, multicenter study was conducted in 15 oncology department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Other studies have also found that dignity helps patients maintain the highest level of independence and control over their own lives [39]. In our series and in a recent study in people with advanced cancer, patients with poorer functional status and worse estimated survival have low levels of perceived dignity [40,41]). Hence the importance of developing programs to address the issue of sense of dignity by considering factors that can help preserve dignity such as maintaining good performance status and good social support.…”
Section: Discussionsupporting
confidence: 58%
“…Other studies have also found that dignity helps patients maintain the highest level of independence and control over their own lives [39]. In our series and in a recent study in people with advanced cancer, patients with poorer functional status and worse estimated survival have low levels of perceived dignity [40,41]). Hence the importance of developing programs to address the issue of sense of dignity by considering factors that can help preserve dignity such as maintaining good performance status and good social support.…”
Section: Discussionsupporting
confidence: 58%
“…In this scenario, the progression of depression and anxiety generally seemed to be more inclined to females and commonly underestimated in males [ 54 ]. In this scenario, it would be necessary for healthcare professionals to improve effective measures purposed at assessing and mitigating depressive symptoms in cases of advanced cancer, thereby improving their mental health, given the high rates of depression in advanced cancer patients [ 55 , 56 , 57 ], due to the difficulty level in performing their daily living activities [ 58 ], which deteriorate further over time [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with advanced cancer generally experience a variety of symptoms, impaired functional status, and the possibility of death [ 36 , 40 , 41 ]. In this study population, we have found that physical symptoms correlated negatively with functional status, in line with earlier findings [ 17 , 42 ].…”
Section: Discussionmentioning
confidence: 99%